2017
DOI: 10.1242/jeb.135137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the control of responses to predator odours in aquatic prey

Abstract: In aquatic systems, chemical cues are a major source of information through which animals are able to assess the current state of their environment to gain information about local predation risk. Prey use chemicals released by predators (including cues from a predator's diet) and other prey (such as alarm cues and disturbance cues) to mediate a range of behavioural, morphological and life-history antipredator defences. Despite the wealth of knowledge on the ecology of antipredator defences, we know surprisingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 123 publications
5
64
0
Order By: Relevance
“…Cues generated through feeding on conspecifics seem to exert stronger responses than cues derived from feeding on other prey species, or from a Daphnia-free diet [22]. Thus, Mitchell et al [237] proposed a distinction between predator cues that are directly originating from the predator itself, dietary cues that are a result or a by-product of the digestion process of the predator, and alarm cues originating from injured prey. These different classes of cues are often difficult to separate experimentally.…”
Section: Defence-inducing Cuesmentioning
confidence: 99%
“…Cues generated through feeding on conspecifics seem to exert stronger responses than cues derived from feeding on other prey species, or from a Daphnia-free diet [22]. Thus, Mitchell et al [237] proposed a distinction between predator cues that are directly originating from the predator itself, dietary cues that are a result or a by-product of the digestion process of the predator, and alarm cues originating from injured prey. These different classes of cues are often difficult to separate experimentally.…”
Section: Defence-inducing Cuesmentioning
confidence: 99%
“…So far, no evidence exists on the potential effect of plastic pellet leachate on predator -prey interactions, in particular on the ability of prey to detect and avoid its predator. These species-specific behaviours are typically mediated by chemical cues [14], whose detection is compromised by chemical pollution [15]. This study assessed experimentally whether prey vigilance and…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that dragonfly larvae are important predators of newt larvae in our study population (Gvoždík & Smolinský, 2015;Smolinský & Gvoždík, 2013). To provide newt larvae with both predator odor and diet cues (Mitchell, Bairos-Novak, & Ferrari, 2017), we fed dragonfly larvae with two living newt larvae at 4-day intervals. The species composition of dragonfly prey was chosen according to species composition and density of newt larvae in a given tank, that is, only I. alpestris, only L. vulgaris, and mixed I. alpestris-L. vulgaris diet.…”
Section: Competition Experimentsmentioning
confidence: 99%